(NdON vUAN lIBRETTO lORENCO s (NkLAWIR u^EBNOE POSOBIEs - (NwOLXFGANG aMADEJ mOCARTs ((NmOSKWAs (NpLANETA MUZYKIs, 2024)
(NdON vUAN WSELAQ DRAMA W DWUH AKTAH w(B. (Na(B. (NmOCARTA NA LIBRETTO lORENCO DA PONTE(B.s
Keywords: (Nu^EBNOE POSOBIEs